Best of the best: A cohort study of race performance characteristics of eminent endurance cyclists - Korf, J.; Johnston, K.; Wang, Y.; Baker, J. (International Journal of Sports Science & Coaching, 2025)
The characteristics of those who advance the frontiers of human capabilities have fascinated scientists for centuries. Studying those who operate at, and advance, the edges of human performance may hold lessons that could benefit athlete development for all ages and stages of competition. To help contribute to this research area, the present study explored race performance characteristics of the world's best endurance cyclists. All race results listed on the Union Cyclisme International database for athletes between the years 2010-2024 (N = 5,168,668 total race observations; N = 107,024 unique athletes [21.12% women and 78.88% men]) were considered. Basic descriptive statistics (e.g., gender, location, confederation, and discipline) were used to describe `eminent` athletes. This eminent sample was further explored relative to their discipline status (i.e., those who race in one discipline, or multiple) and transition patterns. Findings indicate subtle differences between groups in terms of ages to milestones, duration between accomplishing milestones, and transition patterns.